Goodbye Lima. A call for the development of urban-rural models for inhabiting Peruvian territory - Nogales, Lucía (2023)
The displacements produced mainly from the capital to other areas of Peru during the period of quarantine to face the COVID-19 have once again highlighted the lack of capacity of the capital to guarantee a good quality of life for its inhabitants. This article takes these displacements as a symbol of Lima's overflow, and proposes to understand and address the rest of the urban centers of the territory. After reviewing the heterogeneity of these centers, the article questions their true urban character, joining the criticism of hegemonic Euro-American urban theories, which consolidate the traditional urban-rural binomial. The article calls for the development of systems that blur or even dissolve the boundaries between urban and rural, integrating resilient urban-rural systems with a better relationship with their environment and sources of supply in order to face the great challenge of the 21st century, the environmental crisis and its derivatives.